2011
DOI: 10.1165/rcmb.2010-0404oc
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Differentially Affects Eosinophilia and Remodeling in a Model of House Dust Mite Asthma

Abstract: Although a similar prevalence of smoking is evident among patients with asthma and the general population, little is known about the impact of cigarette smoke on the immune inflammatory processes elicited by common environmental allergens. We investigated the impact of exposure to cigarette smoke on house dust mite (HDM)-induced allergic airway inflammation and its consequences for tissue remodeling and lung physiology in mice. BALB/c mice received intranasal HDMs daily, 5 days per week, for 3 weeks to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 46 publications
0
24
1
1
Order By: Relevance
“…Although different in experimental setup, they found some indications for increased allergic inflammation due to cigarette smoke; however, these were less pronounced than in our model. In contrast to our current findings, a recent study by BOTELHO et al [37] using a murine model of established allergic asthma, reported significantly attenuated eosinophilia in BAL fluid of mice exposed to both HDM and cigarette smoke, together with decreased mucus production, and no difference in CD4 + T-cell activation nor airway hyperresponsiveness between HDM and, or cigarette smokeexposed mice.…”
Section: Mechanisms Of Lung Disease Ea Lanckacker Et Alcontrasting
confidence: 99%
See 1 more Smart Citation
“…Although different in experimental setup, they found some indications for increased allergic inflammation due to cigarette smoke; however, these were less pronounced than in our model. In contrast to our current findings, a recent study by BOTELHO et al [37] using a murine model of established allergic asthma, reported significantly attenuated eosinophilia in BAL fluid of mice exposed to both HDM and cigarette smoke, together with decreased mucus production, and no difference in CD4 + T-cell activation nor airway hyperresponsiveness between HDM and, or cigarette smokeexposed mice.…”
Section: Mechanisms Of Lung Disease Ea Lanckacker Et Alcontrasting
confidence: 99%
“…In addition, the variability between commercially available preparations of HDM extract (e.g. endotoxin content) may affect the development of potential Th2 responses in the lung [37].…”
Section: Mechanisms Of Lung Disease Ea Lanckacker Et Almentioning
confidence: 99%
“…To our knowledge, no other reports have assessed the predictive factors of CEP relapse. One possible explanation of our results is the contribution of smoking to the development or maintenance of eosinophilic infiltration in the lung (16). Although our understanding of the pathophysiology of CEP is incomplete, studies of BAL fluid from patients with CEP show elevations of several cytokine, chemokine, and immunomodulatory products (17)(18)(19), which suggests that a multifactorial process is involved in the recruitment of eosinophils into the lung (20).…”
Section: Discussionmentioning
confidence: 83%
“…(8.62%5.14 vs.15.22%4.97, p<0.01) ( Table 14). As it is known that smokers have higher levels of total immunoglobulin E (IgE) 48 and a greater degree of infiltration of inflammatory cells, especially eosinophils 49 , in comparison to nonsmokers, it is most likely that inflammatory processes will lead to airways remodeling and fixed bronchial obstruction, with lower reversibility. As far as skin sensitization established on the basis of skin prick tests is concerned, a greater number of patients from the smoking group (active and former smokers) were sensitized to perennial allergens, while the non-smoking patients with allergic asthma and rhinitis were more sensitized to seasonal allergens.…”
Section: Discussionmentioning
confidence: 99%